CD49d shows superior performance characteristics for flow cytometric prognostic testing in chronic lymphocytic leukemia/small lymphocytic lymphoma. Issue 1 (27th June 2016) - Gooden, Casey E.; Jones, Patricia; Bates, Ruth; Shallenberger, Wendy M.; Surti, Urvashi; Swerdlow, Steven H.; Roth, Christine G.
Abstract : Background: CD49d is emerging as a powerful adverse prognostic marker in chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL). However, flow cytometric testing for CD49d has not yet been widely adopted in the United States, in part due to the lack of establishment of its performance characteristics in the clinical setting, especially in comparison with the more common CLL/SLL prognostic markers CD38 and ZAP‐70. Methods: CD49d expression levels in 124 CLL/SLL cases were assessed among peripheral blood (PB), bone marrow (BM), and lymph node (LN) specimens and correlated with available CD38 and ZAP‐70 expression and cytogenetic findings. For 10 PB/BM specimens, the stability of CD49d, CD38, and ZAP‐70 expression was assessed at <24 hours, 48 hours, 72 hours, and 96 hours. Results: 39% (28 of 71) PB, 56% (18 of 32) BM, and 71% (15 of 21) LN involved by CLL/SLL were CD49d+, using a ≥30% threshold. The mean for the CD49d+ cases was 2.8 standard deviations (SD) above the cutoff for positivity, compared with 1.7 SD for CD38 and 1.1 SD for ZAP‐70. CD49d demonstrated the lowest mean SD (0.91) and coefficient of variation (CV) (8.0%) compared with CD38 (SD = 2.1, CV = 10.4%) and ZAP‐70 (SD = 9.8, CV = 40.5%) in stability studies over a 96‐hours time period. CD49d+ CLL/SLL correlated with trisomy 12 ( P = 0.025) and lack of isolated deletion (13q) ( P = 0.005). CD38+ CLL/SLL correlated with deletion (11q) ( P = 0.025). ZAP‐70 did not correlate with any underlying cytogenetic abnormality. Conclusions: CD49d is a robust adverse prognostic marker in CLL/SLL with superior performance characteristics. © 2016 International Clinical Cytometry Society